SLOGAN DISTRICT AND THE CITY: AN ANALYSIS OF ERRORS IN WRITING OF ENGLISH AND LANGUAGE OF INDONESIA OF PEOPLE OF MINANGKABAU SUMATERA BARAT - Fitri Adona (Masyarakat Linguistik Indonesia Universitas Andalas, 2015)
The slogan of a local brand holds a special and unique role in the creation of a harmonious brand identity. Brand slogan is a phrase that is easily recognized and often remembered and accompanies a brand name in the marketing communications program areas of West Sumatra, Indonesia. The main purpose of a slogan is to support the brand image projected by the brand name and logo. The third element of this brand simultaneously gives the essence of the brand. The problem is, the government of West Sumatra has not been able to find an effective slogan, the which is able to distinguish this area from other areas. The good slogan includes the brand essence, personality, able to reveal the potential of the region and differentiate the brand and logo of a competitor. Brand name, in this case the local name must contain important nformation, especially if it is intended to break through the geographical and cultural boundaries. The cause is expected because of language contact that occurs in bilingual which causing the interplay between B1 and B2. Error analysis of Indonesian and English is a working procedure used by researcher that include the collection of samples, identification of errors contained in the sample, an explanation of the error, the error classification based on the cause, as well as the evaluation or assessment of the level of seriousness of the error. This paper further attempts to minimize the problems encountered Minangkabau people in Indonesian and English writing. Slogan which they make be expected can describe the potential their regions. This study focuses on Indonesian language error and English through slogans made in 12 counties and 7 town in West Sumatra. This paper is trying to identify and describe the mistake to write by Minangkabau people, West Sumatra in the indonesian and English through their regions slogan. The analysis showed errors caused by the interplay of language en each element of the language, such as phonology, morphology, and syntax, and lexicon. The slogan election was also based on geographical naming, legends, community action, and customs of their culture in general. This will enable academic researchers, language teachers, linguists to build a further discussion on mistake of writing Indonesian and English Minangkabau, West Sumatra.